HSPA5 Could Be a Prognostic Biomarker Correlated with Immune Infiltration in Breast Cancer. (20th September 2022) - Zhang, Chao; Liu, Qing; Zhou, Yubo; Hua, Jianfen; Su, Ruijun; Ai, Jun
Abstract : Background . Breast cancer (BC) is a frequent disease in females. The heat shock 70 kDa protein 5 (HSPA5) has recently been discovered to have an important function in tumor growth. However, the biological significance of HSPA5 in BC is unknown. Material and Method . Firstly, The Cancer Genome Atlas (TCGA) database was applied to analyze the expressions of HSPA5 in different cancer types, especially in BC. Then, the LinkedOmics database was used to screen genes coexpressed with HSPA5 in BC, presented by protein-protein interaction (PPI) and analyzed by functional enrichment analyses. Next, the Kaplan-Meier plotter was adopted to study the prognostic significance of HSPA5 and the relation between HSPA5 expression and different clinical factors in BC. Finally, the Tumor Immune Estimation Resource (TIMER) method was adopted to explore the relation between immune infiltration and HSPA5 in BC. Result . HSPA5 was highly expressed in most cancers, including BC. Genes coexpressed with HSPA5 were mainly related to endoplasmic reticulum unfolded protein response, melanosome, thyroid hormone synthesis, N-glycan biosynthesis, and so on. In the survival analysis, high HSPA5 expression indicated a poor prognosis in BC, and the expression of HSPA5 in BC was elevated after the incidence of BC, changing with different clinical factors. In the immune infiltration, HSPA5 was positively correlated with most immune cells. Conclusion . HSPA5 is an oncogene in BC progression, and it is connected with the prognosis and the immune infiltration in BC. Our findings suggest that HSPA5 could be an immunotherapy target and a prognostic biomarker in BC.